Conditions Facilitating the Implementation of Information Communication Technology Integration in the Malaysian Smart School - Mohd Nor, Hajar (2005)
This study reports on the implementation of Information Communication Technology (ICT) integration in the Malaysian Smart School locally known as Sekolah Bestari, specifically in the classroom environment. The main purpose of this study is to look at conditions that facilitated the implementation of ICT integration in the Smart School. At large it asks the question of "Why do teachers in the schools have minimal use of ICT integration in the Smart School" rather than why they do not use them. The study also attempts to discover problems that emerge during the process of integrating ICT in the schools.A qualitative methodology was employed to explore the informants at its natural setting. The data generated by interviews, classroom observations and document reviews were able to capture the teaching and learning process using ICT integration in the classroom situation. Three technology-rich Malaysian secondary schools, the Smart Schools, of different technology levels were carried out to identify the conditions. A total of twenty-one informants, who comprised of twelve teachers, three principals, three heads of curriculum department and three ICT coordinators were interviewed. The teachers formed the primary informants. These teachers represented the four subjects, which had been revised by the curriculum to implement ICT integration in the teaching and learning process. The subjects concerned were English Language, Bahasa Me'.ayu, Mathematics and Science. These teachers had reported different. experiences and perceptions in implementing ICT integration in the schools, hence, enriching the data for this study. The data from primary informants were triangulated with the secondary informants, the principals, heads of curriculum department and ICT coordinators. The data was facilitated by the use of Qualitative N6 data analysis software. The data was coded and categorized relating to common conditions arising from the data. The study had identified the conditions that facilitated the implementation of ICT integration in the Malaysian Smart School. The common conditions that emerged from the data formed the basis guideline for the implementation of ICT in schools. The study confirmed some of the conditions mentioned in the literature, but this study found the depth of those conditions. Two sets of conditions were revealed. They were the essential conditions and the supporting conditions. The essential conditions identified were availability of ICT resources and acquisition of ICT knowledge. The present of these conditions see the possibility of the implementation of ICT integration in the Smart School. If one of these conditions was not present then implementation of ~ ~ ~ ' i n t e ~ r awtoiuoldn n ot take place. The next set of conditions was the supporting conditions. The supporting conditions comprised of the accessibility to ICT resources, existence of support, desire to change, school practices, influence of external forces and teacher's commitment to the innovation determined continuous implementation of ICT integration in the schools. The findings demonstrated a relationship between the presence of these conditions and the continuation of implementation of ICT integration. It was found that the presence of these conditions in schools enabled them to continue with the implementation of ICT integration. However, the lack or absence of these conditions resulted in the slow down or discontinuation of the integration of ICT in the schools.The findings also revealed that teachers in the study employed four levels of approaches in integrating ICT in the schools. These teachers integrated ICT as verbal resources at level one, as printed resources at level two, as hands-on experience at level three and a combination of all the approaches at level four. It seemed that the levels of approach were influenced by the presence and absence of the conditions that facilitated the implementation of ICT integration in the Smart School. The study also discovered problems that the teachers faced during the process of integrating ICT in the schools. The issues that emerged in the implementation of ICT integration in the Malaysian technology-rich school, the Smart School were time factor, course content and technical malfunction. Recommendations were made and implication for theory and practice were also proposed for possible course of actions for the practitioners in implementing ICT integration in the schools.